2021
DOI: 10.3390/ijms22094697
|View full text |Cite
|
Sign up to set email alerts
|

Role of miRNA-19a in Cancer Diagnosis and Poor Prognosis

Abstract: Cancer is a multifactorial disease that affects millions of people every year and is one of the most common causes of death in the world. The high mortality rate is very often linked to late diagnosis; in fact, nowadays there are a lack of efficient and specific markers for the early diagnosis and prognosis of cancer. In recent years, the discovery of new diagnostic markers, including microRNAs (miRNAs), has been an important turning point for cancer research. miRNAs are small, endogenous, non-coding RNAs that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 128 publications
0
18
0
Order By: Relevance
“…MicroRNAs (miRNAs) are 19-24-nucleotide-(nt-) long noncoding, single-stranded, small RNAs, which bind to target mRNAs to regulate gene expression [5]. It is reported that miRNAs are involved in various physiological processes including cell proliferation, differentiation, apoptosis, tissue invasion and migration, and angiogenesis [6][7][8]. Li et al found that miR-202-3p inhibits the proliferation, migration, and invasion of lung adenocarcinoma cells through lowering of the matrix metalloproteinase-1 (MMP-1) [9].…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are 19-24-nucleotide-(nt-) long noncoding, single-stranded, small RNAs, which bind to target mRNAs to regulate gene expression [5]. It is reported that miRNAs are involved in various physiological processes including cell proliferation, differentiation, apoptosis, tissue invasion and migration, and angiogenesis [6][7][8]. Li et al found that miR-202-3p inhibits the proliferation, migration, and invasion of lung adenocarcinoma cells through lowering of the matrix metalloproteinase-1 (MMP-1) [9].…”
Section: Introductionmentioning
confidence: 99%
“…A total of 20 miRNAs were identified as potential targets of LINC01087 (Analysis 3— Figure 3 , Table S12 ). Most of them had already been involved in carcinogenesis, such as miR-19a-3p and miR-181-5p [ 49 , 50 ]. Furthermore, 4 of the 20 miRNAs belonged to the let-7 miRNA family (i.e., hsa-let-7a-5p, hsa-let-7d-5p, hsa-let-7e-5p, hsa-miR-98-5p).…”
Section: Resultsmentioning
confidence: 99%
“…The overexpression of TGF-β in tumor cells exerts dual effects: regulating the expression of PD-L1 and VEGF and affecting biomarkers associated with the modulation of immune response and evasion, including Foxp3/Treg, MDSC, Th1/Th2 balance, and macrophage cells [ 9 , 10 , 17 , 18 , 19 , 49 , 56 , 57 , 58 ]. HIFs and TGF-β are biomarkers associated with the expression of the AXL gene, which is highly overexpressed in tumors with a loss of VHL function and is associated with a poor response to biologically targeted molecules [ 59 , 60 , 61 , 62 , 63 ]. Based on published data generated by others and data generated in our laboratory, Figure 4 is presented to illustrate the potential role of miR-210, miR-155, TGF-β, and HIFs individually or collectively in the regulation of multiple targets.…”
Section: Discussionmentioning
confidence: 99%
“…The data generated in the nine ccRCC cell lines and in the six biopsies showed that miR-17 and miR-19a were downregulated, while miR-34a was upregulated in cell lines with and without sarcomatoid differentiation and downregulated in the six ccRCC tumor biopsies. miR-17, -19a, and -34a were identified to function either as tumor suppressors or as oncogenes [ 49 , 53 , 63 , 68 , 69 , 70 ]. The function of these genes is likely determined by tumor types, cancer stage, and the relative expression levels of these miRs.…”
Section: Discussionmentioning
confidence: 99%